Experimental Study on the Difference of Shale Mechanical Properties - Qi Liu; Bing Liang; Weiji Sun; Hang Zhao (Advances in Civil Engineering)
This paper studies the anisotropic characteristics of shale and the difference in mechanical performance between deep shale and outcrop shale. The outcrop shale was collected from the Shuanghe section in Changning County, southern Sichuan, and the deep shale was collected from the Wells Yi201 and Lu202. Study their basic mechanical parameters, failure modes, and wave velocity responses through laboratory tests. Research shows that with the increase of bedding angle, the deformation mode has the trend from elastic deformation to plastic deformation in high-stress state. When the bedding angles are 0°, 30°, and 45°, the weak bedding surface plays a leading role in the formation of the failure surface trend. As the bedding angle increases to 60° and 90°, its influence is weakened. The tensile strength, elastic modulus, and wave velocity decrease with the increase of bedding angle. The compressive strength and Poisson’s ratio have the law of U-type change, there are higher values at 0° and 90°, and the lowest values are at 30°. The brittleness index first increases and then decreases with the increase of the bedding angle. The tensile strength and Poisson’s ratio of outcrop shale and deep shale are close, but the compressive strength of deep shale is only 1/3 of outcrop shale, the elastic modulus is only 3/4 of outcrop shale, and the failure of deep shale is accompanied by instability failure.